2022
DOI: 10.3390/v15010132
|View full text |Cite
|
Sign up to set email alerts
|

Construction of a Chikungunya Virus, Replicon, and Helper Plasmids for Transfection of Mammalian Cells

Abstract: The genome of Alphaviruses can be modified to produce self-replicating RNAs and virus-like particles, which are useful virological tools. In this work, we generated three plasmids for the transfection of mammalian cells: an infectious clone of Chikungunya virus (CHIKV), one that codes for the structural proteins (helper plasmid), and another one that codes nonstructural proteins (replicon plasmid). All of these plasmids contain a reporter gene (mKate2). The reporter gene in the replicon RNA and the infectious … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 73 publications
0
5
0
Order By: Relevance
“…The recombinant virus particles are mostly called virus‐like particles (VRPs). They are also known as virus‐like replicon particles (VLPs) 8–10 . SFV VRPs have been commonly used for cancer therapy and vaccine development in various animal models, and to some extent, in clinical trials 8,11–13 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The recombinant virus particles are mostly called virus‐like particles (VRPs). They are also known as virus‐like replicon particles (VLPs) 8–10 . SFV VRPs have been commonly used for cancer therapy and vaccine development in various animal models, and to some extent, in clinical trials 8,11–13 …”
Section: Discussionmentioning
confidence: 99%
“…They are also known as virus-like replicon particles (VLPs). [8][9][10] SFV VRPs have been commonly used for cancer therapy and vaccine development in various animal models, and to some extent, in clinical trials. 8,[11][12][13] A therapeutic cancer vaccine named Vvax001 was recently tested in a first-in-human phase I trial against human papillomavirus (HPV)-induced cancers.…”
Section: Discussionmentioning
confidence: 99%
“…CHIKV is categorized as a highly pathogenic alphavirus, and live CHIKV should be handled in the P3 laboratory, which hampers the study of CHIKV. Therefore, the CHIKV replicon, virus-like particles (VLPs) and pseudoviruses are alternatives widely used in exploring CHIKV molecular virology and pathogenesis [35][36][37]. In addition, a specific viral protein used as a bait protein for yeast two-hybrid systems, Co-IP or GST pull-down, combined with MS, is commonly used to discover protein-protein interactions and interacting domains [38][39][40].…”
Section: Discussionmentioning
confidence: 99%
“…While most studies with hRSV use MOIs between 0.1 and 3.0 [ 24 , 29 , 30 , 31 , 45 , 46 ] we decided to use an MOI of 10 to be able to detect ultrastructural changes, which is one of the limitations of this study. In previous studies with Zika (ZIKV) [ 47 ] and Chikungunya (CHIKV) [ 48 ] virus, we used low MOIs for thin-section TEM. However, preliminary experiments with hRSV at MOIs of 0.1 and 1.0 showed that detecting ultrastructural changes in the mitochondrion was extremely challenging at these MOIs (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…However, preliminary experiments with hRSV at MOIs of 0.1 and 1.0 showed that detecting ultrastructural changes in the mitochondrion was extremely challenging at these MOIs (data not shown). Furthermore, in the cases of CHIKV [ 48 ] and ZIKV [ 47 ] infections at an MOI of 1.0 lead to complete destruction of the cellular monolayer within the first 72 h.p.i. ; however, with hRSV, infection at an MOI of 10 does not result in complete disruption of the monolayer even at 96-h.p.i.…”
Section: Discussionmentioning
confidence: 99%